Health Psychology Of Key To Sustaining And Thriving Of Human Well Being: Self Control, Conscientiousness, And Adverse Health Behavior - Gusti Jhoni Putra (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2014)
This paper explained that a description of several adverse health behavior and their health care cost impacts, it was argues that, rather than a focus on external environmental factors, the intrinsic constructs of self control and Conscientiousness should be given more priority in explaining and combating these behaviours. Self control and Conscientiousness have profound influences on an individual’s choice to succumb to temptation or resist it, respond impulsively or with self restraint, or seek immediate versus delayed gratification. Method used literature reviews from authoritative databases. Several examples are offered to illustrate the impact of self control and Conscientiousness on a mix of common adverse health behaviors and positive health behaviors, and through these examples it is argued that self control and Conscientiousness are unappreciated constructs in health psychology. Several recommendations for improving self control and Conscientiousness are discussed.